Impact Of Online Learning On Students With Special Reference To Under-Graduate (UG) Students Of Golaghat District, Assam (International Journal of Food and Nutritional Sciences, 2022)
The term "COVID 19" refers to the corona virus disease that first appeared in 2019 and was discovered in Wuhan, China, in December of that same year. This was a pandemic viral sickness that severely damaged the biosphere as well as the lives of all living things. It had an impact on people on all levels of devastation, including their bodily, mental, and psychological health as well as their social, economic, cultural, educational, and political lives. It also had a detrimental impact regardless of one's age, gender, socioeconomic status, etc. Every group in the human population had been affected by the COVID-19 pandemic, including the elderly, the young, the young at heart, and children. In this regard, the mental, physical, and psychological health of students was impaired by the impact of COVID-19, and the education of students was also negatively impacted. This research study aims to investigate the effects of online instructions on undergraduate students. Data were gathered using a primary approach, such as a questionnaire, and secondary data were also gathered from a variety of study-related sources, including articles, journals, books, census data, etc.. In light of the fact that online classes harm students' health, result in strengthen learners' departure from real biosphere, weaken learners' logical aptitude, and facilitate face-to-face interactive association, this study explains the detrimental effects of online education on undergraduate students.